Checklist of vespid wasps (Hymenoptera: Vespidae) of Goa, India, with new records and a key to species - Gawas, Sandesh M.; Kumar, P. Girish; Gupta, Ankita; Sureshan, P.m. (Zootaxa, 2019)
This study on the vespid fauna (Hymenoptera: Vespidae) reports 33 species belonging to 22 genera and four subfamilies from the state of Goa, India. Of these, 26 species, 18 genera, and two subfamilies are newly recorded from Goa. Illustrated keys to the genera and species of vespid wasps of Goa along with notes on their geographical distribution are provided.